The Economic Effects of Potential EU Tariff Sanctions on Russia — A Sectoral Approach - Olim Latipov; Christian Lau; Kornel Mahlstein; Simon Schropp (Intereconomics)
Abstract As part of its sanctions regime, the United States recently announced the imposition of punitive import tariffs on 570 product groups from Russia. The European Union may follow suit and enact sanctions on Russia that mirror the US sanctions in scale and scope. Using a sector-specific partial-equilibrium model, we quantify the impact of such mirror sanctions. We find they would inflict on Russia welfare losses of at least $996 million per year — at an overall cost of $150 million to EU consumers. Breaking down these totals in a sectoral analysis, we find that mirroring the US action would produce mixed results from the EU’s perspective. On the one hand, tariff sanctions cover a number of sectors whose inclusion would inflict particularly large welfare losses for Russia and/or high welfare gains for the EU. On the other hand, mirror sanctions would bring significant inefficiencies for the EU. For example, in 72 sectors, higher tariffs would inflict greater harm on the EU than on the Russian economy, causing EU losses in excess of $560 million. Thus, consistent with the spirit of international coordination and alignment, the EU may consider adjusting the suite of tariff sanctions rather than simply adopting the US package.